The fattening of mud crab, scylla serrata, in a floating cage installed in the Lagatik river and fed with fresh fish and commercial crustacean pillet feed - Cahilig, Diony G. (University of the Philippines in the Visayas, 1995)
Six feeding treatments and their feeding rates (% body weight) namely: I, 100% trash fish (TF), 6% feeding rate ; II, 80% TF and 20% commercial crustacean pellet feed (CCPF), 5.4% feeding rate ; III, 60% TF and 40% CCPF, 4.8% feeding rate ; IV, 40% TF and 60% CCPF, 4.2% feeding rate ; V, 20% TF and 80% CCPF, 3.6% feeding rate ; and VI, 100% CCPF, 3% feeding rate were tested to determine the effect on weight gain, condition factor, feed conversion ratios and the economic feasibility of fattening mud crab in floating cages. Result shows that male crabs have a significantly higher (P<.05) weight gain and condition factor than female, while no significant difference was observed on percentage weight gain and feed conversion ratio. On the effect of feeds Treatment II obtained a significantly low result (P<.05) on weight gain and mean daily weight gain. Treatment VI had a significantly high result on percentage weight gain (P<.05 and feed conversion ratio (P<.01) but showed no significant difference on the condition factor. However, crabs in Treatment I obtained mean benefit cost ratio of 0.41, considered feasible over the other treatments. Fattening of female crabs was found to be more feasible than males, with benefit cost ratio ranging from 0.51 to 0.64 while that of the males ranged only from -0.08to 0.17.